2003
DOI: 10.1023/a:1024000821368
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The development of organic-inorganic hybrids composed of hydroxyapatite and organic polymers is attractive because of their novelty in being materials that show a bone-bonding ability, i.e. bioactivity, and because they have mechanical properties similar to those of natural bone. The biomimetic process has received much attention for fabricating such a hybrid, where bone-like apatite is deposited under ambient conditions on polymer substrates in a simulated body fluid (SBF) having ion concentrations nearly equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(9 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Synthetic polymer substrates are also useful to prepare apatite-polymer composites. We (Miyazaki et al 2003c;Kawai et al 2004) reported that aromatic polyamides containing carboxyl groups (polyamide-COOH) or sulphonic (-SO 3 H) groups (polyamide-SO 3 H; Konagaya & Tokai 2000) show apatite-forming ability in 1.5SBF when they contained CaCl 2 . The amount of apatite formed and the rate of formation increased with increasing amounts of functional groups in the polyamides.…”
Section: Bioactive Coatingmentioning
confidence: 99%
“…Synthetic polymer substrates are also useful to prepare apatite-polymer composites. We (Miyazaki et al 2003c;Kawai et al 2004) reported that aromatic polyamides containing carboxyl groups (polyamide-COOH) or sulphonic (-SO 3 H) groups (polyamide-SO 3 H; Konagaya & Tokai 2000) show apatite-forming ability in 1.5SBF when they contained CaCl 2 . The amount of apatite formed and the rate of formation increased with increasing amounts of functional groups in the polyamides.…”
Section: Bioactive Coatingmentioning
confidence: 99%
“…Even synthetic polymer substrates containing carboxyl groups also can be coated with bone-like apatite. Miyazaki et al [75] reported that aromatic polyamides containing carboxyl groups [76] showed apatite-forming ability in 1.5SBF when they contained CaCl 2 (figure 6). The apatite layer formed was attached tightly to the polymer.…”
Section: Coating Of Bone-like Apatite On Polymersmentioning
confidence: 99%
“…It was also reported that polyamide films containing carboxy groups have the ability to induce the deposition of HAp crystals. 11 Moreover, the HAp crystals were effectively precipitated on a collagen membrane after immersing into citric acid (CA)-containing SBF. 12 The reason was considered to be that the hydroxyl group of CA could adhere to the collagen membrane through hydrogen bonding with the hydrophilic groups ( e.g.…”
Section: Introductionmentioning
confidence: 99%